Fundamental Concepts and Goals of Education in the Perspective of Islamic Educational Philosophy - Siregar, Pamonoran; Usiono, Usiono; Saputra, Anri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to discover the fundamental concepts and goals of education from the perspective of Islamic education. Islamic Educational Philosophy is a conceptual framework on education based on the teachings of Islam, concerning the nature of human potential to be nurtured, developed, and guided to become a Muslim whose entire personality is imbued with Islamic teachings. This research is a literature study that collects information and data from relevant scholarly articles and books. The findings of this study indicate that education in the perspective of Islamic educational philosophy is based on the principle of Tawhid, with the primary goal of shaping morally upright and God-fearing individuals. The Quran and Sunnah serve as the primary sources of guidance, while the teaching methods emphasize active learning and direct experience. The practical implications of Islamic educational philosophy include the development of a curriculum based on the Quran and Sunnah, experience-based learning, character development, and a holistic approach to education. By understanding the basic concepts of Islamic educational philosophy, educators can design educational programs that align with Islamic values and meet the holistic needs of students.